Viability of Trichomonas vaginalis in Copan Universal Transport Medium and eSwab Transport Medium - Rivers, C. A. (American Society for Microbiology (ASM), 2008)
We compared the use of universal transport medium and eSwab transport medium held at room temperature or 37°C to bedside inoculation and immediate incubation of culture media for the detection of Trichomonas vaginalis. There were no significant culturable differences in the sensitivity of either of the transport media to that of bedside inoculation.